Macrophage Inflammatory Protein-1 Alpha, a Potential Biomarker for Predicting Left Atrial Remodeling in Patients With Atrial Fibrillation - Chen, Yung-Lung; Wang, Hui-Ting; Lin, Pei-Ting; Chuang, Jiin-Haur; Yang, Ming-Yu (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Left atrial (LA) remodeling itself is an independent risk factor for ischemic stroke and mortality, with or without atrial fibrillation (AF). Macrophage inflammatory protein-1 alpha (MIP-1α) has been reported to be involved in the induction of autoimmune myocarditis and dilated cardiomyopathy. Little is known about whether MIP-1α can be used to predict LA remodeling, especially in patients with AF. Methods: We prospectively enrolled 78 patients who had received a cardiac implantable electronic device due to sick sinus syndrome in order to define AF accurately. AF was diagnosed clinically before enrollment, according to 12-lead electrocardiography (ECG) and 24-h Holter test in 54 (69%) patients. The serum cytokine levels and the mRNA expression levels of peripheral blood leukocytes were checked and echocardiographic study was performed on the same day within 1 week after the patients were enrolled into the study. The 12-lead ECG and 24-h Holter test were performed on the same day of the patients' enrollment, and the device interrogation was performed every 3 months after enrollment. The enrolled patients were clinically followed up for 1 year. Results: There was no difference in baseline characteristics, cytokine levels and mRNA expression between patients with and without AF. Larger LA volume was positively correlated with higher levels of MIP-1α (r = 0.461, p ≤ 0.001) and the atrial high-rate episodes (AHREs) burden (r = 0.593, p < 0.001), and negatively correlated with higher levels of transforming growth factor (TGF)-β1 (r = −0.271, p = 0.047) and TGF-β3 (r = −0.279, p = 0.041). The higher AHREs burden and MIP-1α level could predict LA volume independently. The mRNA expression of RORC was negatively associated with the MIP-1α level. Conclusions: This study showed that higher MIP-1α was significantly associated with LA remodeling and may have the potentials to predict LA remodeling in terms of a larger LA volume, and that circadian gene derangement might affect the expression of MIP-1α.